2017
DOI: 10.1038/s41598-017-04517-8
|View full text |Cite
|
Sign up to set email alerts
|

Boronic Acid-Modified Magnetic Fe3O4@mTiO2 Microspheres for Highly Sensitive and Selective Enrichment of N-Glycopeptides in Amniotic Fluid

Abstract: Although mesoporous materials and magnetic materials are used to enrich glycopeptides, materials sharing both mesoporous structures and magnetic properties have not been reported for glycopeptide analyses. Here we prepared boronic acid-modified magnetic Fe3O4@mTiO2 microspheres by covalent binding of boronic acid molecules onto the surfaces of silanized Fe3O4@mTiO2 microspheres. The final particles (denoted as B-Fe3O4@mTiO2) showed a typical magnetic hysteresis curve, indicating superparamagnetic behavior; mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…With the help of hydrophobic poly(methyl methacrylate) (PMMA) nanobeads that were used to remove hydrophobic peptides in HRP digests, the recovery was estimated to be increased from 78% to 90%. This work come up with a good notion of synergistic enrichment, which was used in Shi's report . Moreover, hydrophilic poly(phenol‐formaldehyde resin) and 3‐isocyanatopropyltriethoxysilane were applied to immobilize APBA onto the graphene and zeolitic imidazolate framework‐8, respectively .…”
Section: Nanomaterials In Glycoproteomicsmentioning
confidence: 99%
“…With the help of hydrophobic poly(methyl methacrylate) (PMMA) nanobeads that were used to remove hydrophobic peptides in HRP digests, the recovery was estimated to be increased from 78% to 90%. This work come up with a good notion of synergistic enrichment, which was used in Shi's report . Moreover, hydrophilic poly(phenol‐formaldehyde resin) and 3‐isocyanatopropyltriethoxysilane were applied to immobilize APBA onto the graphene and zeolitic imidazolate framework‐8, respectively .…”
Section: Nanomaterials In Glycoproteomicsmentioning
confidence: 99%
“…In recent years, some reports of magnetic materials as immobilized enzyme supports have usually involved pre‐modification of Fe 3 O 4. 27, 28 It has been reported that magnetic components can be combined with TiO 2 to form multifunctional nanomaterials 29–32 …”
Section: Introductionmentioning
confidence: 99%
“…However, because of the inherently low abundance of glycoproteins and the complexity of biological samples, it is almost impossible to directly identify glycoproteins without any pretreatment of samples . Many methods have been developed for glycoprotein enrichment, such as lectin affinity chromatography , HILIC , hydrazide chemistry , and boronate affinity chromatography . Lectin affinity chromatography based on affinity interaction between lectin and glycans shows high specificity.…”
Section: Introductionmentioning
confidence: 99%
“…However, because Article Related Abbreviations: EGDMA, ethylene glycol dimethacrylate; GO, graphene oxide; HRP, horseradish peroxidase; PEEK, poly(ether ether ketone); poly(VPBA-EGDMA), poly(vinylphenylboronic acid-ethylene glycol dimethacrylate); SWNT, single-walled carbon nanotube; VPBA, vinylphenylboronic acid of the inherently low abundance of glycoproteins and the complexity of biological samples, it is almost impossible to directly identify glycoproteins without any pretreatment of samples [4,5]. Many methods have been developed for glycoprotein enrichment, such as lectin affinity chromatography [6,7], HILIC [8], hydrazide chemistry [9], and boronate affinity chromatography [10,11]. Lectin affinity chromatography based on affinity interaction between lectin and glycans shows high specificity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation